(untitled) (Raparin Journal of Humanities (RJH), 2024)
Agricultural land is vital for production, but its size is shrinking each year. Efforts are being made to enhance it by agricultural institutions and organizations. This study addresses the problem of inefficient use of agricultural land resources, lack of suitable programs, and poor management, which leads to declining soil fertility and reduced productivity. The aim of this study to find better ways to use agricultural land by implementing improvement programs and assessing their impact on crop productions, to modernize agriculture. The data has come from 150 farmers, including 87 who have not properly followed soil enhancement programs, were analyzed. The results present that the growth of orchards reduces agricultural land area and per-acre productivity. Only 10% of gardens have expert supervision, and immoderate construction of new gardens further reduces agricultural land each year. The study provides recommendations to improve and preserve agricultural soil at local and regional levels.